Cultural diversity : a primer for the human services - Diller, Jerry V. (Brooks/Cole : Wadsworth, 1999)
What it means to be culturally competent. Understanding racism and prejudice. Understanding culture and cultural differences. Ethnic children, parenting, and families. Mental health issues. Bias in service delivery. Critical issues in working with culturally different clients...